2018
DOI: 10.1016/j.neuropharm.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Probing GABAA receptors with inhibitory neurosteroids

Abstract: γ-aminobutyric acid type A receptors (GABAARs) are important components of the central nervous system and they are functionally tasked with controlling neuronal excitability. These receptors are subject to post-translational modification and also to modulation by endogenous regulators, such as the neurosteroids. These modulators can either potentiate or inhibit GABAAR function. Whilst the former class of neurosteroids are considered to bind to and act from the transmembrane domain of the receptor, the domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 50 publications
2
37
1
Order By: Relevance
“…For 3α,5α-steroids: THDOC 3, alphaxalone 4, 6-Azi-OAP 6and 21-pTFDBzox-AP itself (16), 3α,5β-steroid (pregnanolone, 1) and 6-azi-OP 5, the agreement between IC 50 and EC 50 was very good. Furthermore, pregnenolone sulfate, a 3β-steroid that inhibits GABA currents, 31 neither bound to the 21-pTFDBzox-AP site nor enhanced desensitization. Considering that the binding studies were carried out in much more dilute suspensions than the photolabeling studies, we regard the pharmacological evidence establishing that photoincorporation was occurring in the site that was responsible for enhancing desensitization to be strong.…”
Section: Discussionmentioning
confidence: 96%
“…For 3α,5α-steroids: THDOC 3, alphaxalone 4, 6-Azi-OAP 6and 21-pTFDBzox-AP itself (16), 3α,5β-steroid (pregnanolone, 1) and 6-azi-OP 5, the agreement between IC 50 and EC 50 was very good. Furthermore, pregnenolone sulfate, a 3β-steroid that inhibits GABA currents, 31 neither bound to the 21-pTFDBzox-AP site nor enhanced desensitization. Considering that the binding studies were carried out in much more dilute suspensions than the photolabeling studies, we regard the pharmacological evidence establishing that photoincorporation was occurring in the site that was responsible for enhancing desensitization to be strong.…”
Section: Discussionmentioning
confidence: 96%
“…Steroids with a sulfate rather than a hydroxyl at the 3-carbon are also GABA A R NAMs thought to act at sites distinct from GABA A R PAMs (5,13,14,17,32). The precise location of this site is unclear, but crystallographic studies have demonstrated a possible binding site between TM3 and TM4 on the intracellular end of the α-subunit TMD (17,24).…”
Section: Introductionmentioning
confidence: 99%
“…While 3β-OH NS and PS both inhibit GABA A Rs, they likely act via interactions with distinct sites (5,13,14,16,17,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…The site of inhibitory neurosteroid binding to GABA A R is unknown. However, it is thought to be outside the pore, and distinct from the binding sites of both potentiating neurosteroids and picrotoxinin (GABA A R open channel blocker) binding [115]. The evidence for this is that inhibition is not voltage-dependent, as would be expected for an open channel blocker, the inhibitory effects of pregnenolone sulfate and picrotoxin are additive, and, unlike potentiating neurosteroids, pregnenolone sulfate on the inner membrane leaflet cannot affect GABA A R. Neurosteroid mediated GABA A R inhibition is more effective at higher GABA concentrations, suggesting that the binding site is exposed by receptor activation [116].…”
Section: Gabamentioning
confidence: 99%